2021
DOI: 10.1073/pnas.2019318118
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss drives acetylcholine- and somatostatin interneuron–mediated gating of hippocampal activity to inhibit memory consolidation

Abstract: Sleep loss disrupts consolidation of hippocampus-dependent memory. To characterize effects of learning and sleep loss, we quantified activity-dependent phosphorylation of ribosomal protein S6 (pS6) across the dorsal hippocampus of mice. We find that pS6 is enhanced in dentate gyrus (DG) following single-trial contextual fear conditioning (CFC) but is reduced throughout the hippocampus after brief sleep deprivation (SD; which disrupts contextual fear memory [CFM] consolidation). To characterize neuronal populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(105 citation statements)
references
References 78 publications
(156 reference statements)
10
80
2
Order By: Relevance
“…Our lab has recently demonstrated that SD also profoundly disrupts principal neuron activity in the hippocampus. We found that SD decreases neuronal activity-driven phosphorylation of ribosomal protein S6 throughout the dorsal hippocampus, suggesting decreased neuronal activity ( Delorme et al, 2021 ). This is consistent with previous findings from our lab, where IEG Arc ’s messenger ribonucleic acid (mRNA) and protein expression is reduced in DG after a period of SD ( Delorme et al, 2019 ).…”
Section: State-dependent Regulation Of Interneuron Activity During Memory Consolidationmentioning
confidence: 97%
See 4 more Smart Citations
“…Our lab has recently demonstrated that SD also profoundly disrupts principal neuron activity in the hippocampus. We found that SD decreases neuronal activity-driven phosphorylation of ribosomal protein S6 throughout the dorsal hippocampus, suggesting decreased neuronal activity ( Delorme et al, 2021 ). This is consistent with previous findings from our lab, where IEG Arc ’s messenger ribonucleic acid (mRNA) and protein expression is reduced in DG after a period of SD ( Delorme et al, 2019 ).…”
Section: State-dependent Regulation Of Interneuron Activity During Memory Consolidationmentioning
confidence: 97%
“…VIP+ interneurons inhibit SST+ interneurons in the circuit. Left: During a period of post-learning sleep, principal cells and PV+ interneurons generally become more active ( Ognjanovski et al, 2014 ), while SST+ interneurons are relatively quiescent (due to lower acetylcholine-mediated activation in NREM sleep) ( Delorme et al, 2021 ). Some principal neurons (engram neurons) will become selectively more active, and may form new and/or stronger synaptic connections ( Clawson et al, 2021 ).…”
Section: Pv+ and Sst+ Interneurons Are Critical Regulators Of Memory Encoding Storage And Recallmentioning
confidence: 99%
See 3 more Smart Citations